The 'Erfahrraum' : a pedagogical model for designing educational technologies in dual vocational systems - Schwendimann, Beat A. [Verfasser]; Cattaneo, Alberto A.P. [Verfasser]; Dehler Zufferey, Jessica [Verfasser]; Gurtner, Jean-Luc [Verfasser]; Betrancourt, Mireille [Verfasser]; Dillenbourg, Pierre [Verfasser] (My University, 2015)
"Vocational education taking place in the dual contexts of workplace and school often lacks integration of concrete experiences with theoretical knowledge. The interplay between workplace and school contexts and their often antagonistic priorities call for a specific model that transforms these divergences into learning opportunities and connects different forms of knowledge into an integrated body of knowledge that contributes to developing vocational competence. This paper presents a multidimensional pedagogical model, called the 'Erfahrraum', for the design and implementation of educational technologies as a way to foster this integration in initial dual vocational education and training (VET). The 'Erfahrraum' model informs the design of shared spaces for capturing and reflecting on experiences made in different contexts in which VET takes place. The model particularly emphasises the importance of shared reflection processes to turn concrete experiences into relevant integrated knowledge. Examples of implementations in different professions using a range of different technologies illustrate the power of the 'Erfahrraum' model." (Authors' abstract)
Keywords: S 1.3 Berufliche Erstausbildung; L 4 Medien & Technologien; Berufsausbildung; Lernort; Bildungstechnologie; Erfahrungswissen